SURFACE WATER QUALITY. STUDY CASE: RIVER GALDA, ALBA COUNTY, ROMANIA - TRUȚA, Roxana Maria; POPA, Maria (Studia Universitatis Babeș-Bolyai Ambientum, 2015)
Pollution is affecting all of the water characteristics, and generate degradation of physical, chemical and biological parameters. A strong pollution phenomena can lead to ecological disruption, or destruction of aquatic flora and fauna. To avoid complete destruction of the hydrosphere is necessary to adopt pollution prevention and cessation. This study is a water quality assessment on river Galda from Alba County. Water quality assessment was done by analyzing the physicochemical parameters of water and by analyzing the existing benthic community in the rivers waters. These parameters are relevant to assess the rivers pollution and its variation over time. Study results revealed a proportional increase of pollution with the number of inhabitants in the river area. A major influence on river Galda water quality is the agricultural and farming land near the river, also industrial activity, which generate in about 10 years, a significant degradation of environmental quality.